2010
DOI: 10.1002/dvdy.22501
|View full text |Cite
|
Sign up to set email alerts
|

Fgfr1 and the IIIc isoform of Fgfr2 play critical roles in the metanephric mesenchyme mediating early inductive events in kidney development

Abstract: Fibroblast growth factor receptors (Fgfrs) have critical roles in kidney development. FgfrIIIb is thought to act in epithelium, while FgfrIIIc functions in mesenchyme. We aimed to determine roles of Fgfr2IIIc in kidney development. Mice with deletion of Fgfr2IIIc (Fgfr2IIIc−/−) had normal kidneys. Combination of Fgfr2IIIc−/− with conditional deletion of Fgfr1 in metanephric mesenchyme (MM) (Fgfr1Mes−/−Fgfr2IIIc−/−) had small but identifiable MM at E10.5, expressing mesenchymal markers including Eya1, Six2, Pax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…Finally, glial cell line-derived neurotrophic factor (Gdnf), the ligand for Ret expressed on ureteric tips, was present in the thin remnant metanephric mesenchyme tissues at E10.5, but absent at E11.5, leading to arrest of ureteric bud outgrowth and no branching. A follow up study in which mice with Pax3cre-mediated deletion of Fgfr1 and a global deletion of the IIIc isoform of Fgfr2 ( Pax3cre; Fgfr1 fl/fl ; Fgfr2IIIc−/− ) had a similar, albeit clearly less severe, defect in metanephric mesenchyme formation at E10.5 compared to Pax3cre; Fgfr1 fl/fl ; Fgfr2 fl/fl mice; moreover, we noted low levels of Fgfr2IIIb isoform mRNA expression in cap mesenchyme of both Pax3cre; Fgfr1 fl/fl ; Fgfr2IIIc−/− and control mice, suggesting that IIIb isoforms of Fgfrs may signal in mesenchymal tissues (and not just epithelium as has been long believed) [44]. Taken together, these studies revealed redundant and critical roles of Fgfr1 and Fgfr2 in establishing and sustaining early metanephric mesenchyme.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Finally, glial cell line-derived neurotrophic factor (Gdnf), the ligand for Ret expressed on ureteric tips, was present in the thin remnant metanephric mesenchyme tissues at E10.5, but absent at E11.5, leading to arrest of ureteric bud outgrowth and no branching. A follow up study in which mice with Pax3cre-mediated deletion of Fgfr1 and a global deletion of the IIIc isoform of Fgfr2 ( Pax3cre; Fgfr1 fl/fl ; Fgfr2IIIc−/− ) had a similar, albeit clearly less severe, defect in metanephric mesenchyme formation at E10.5 compared to Pax3cre; Fgfr1 fl/fl ; Fgfr2 fl/fl mice; moreover, we noted low levels of Fgfr2IIIb isoform mRNA expression in cap mesenchyme of both Pax3cre; Fgfr1 fl/fl ; Fgfr2IIIc−/− and control mice, suggesting that IIIb isoforms of Fgfrs may signal in mesenchymal tissues (and not just epithelium as has been long believed) [44]. Taken together, these studies revealed redundant and critical roles of Fgfr1 and Fgfr2 in establishing and sustaining early metanephric mesenchyme.…”
Section: Introductionsupporting
confidence: 66%
“…As noted earlier, while Pax3cre; Fgfr1 fl/fl ; Fgfr2 fl/fl mice had aborted ureteric buds, they often had two ureteric buds per Wolffian duct [43]. Similarly, Pax3cre; Fgfr1 fl/fl ; Fgfr2IIIc−/− and Pax3cre; Fgfr1 fl/fl ; Fgfr2 LR/LR mice had multiple and/or displaced ureteric buds [44, 45]. These defects raised two questions: first, was loss of either Fgfr1 or Fgfr2 alone sufficient to drive the ureteric induction defects (and what were the consequences of the induction defects); and second, which mesenchymal tissue(s) was(were) the receptor(s) acting in to constrain the ureteric induction site (given that the Pax3cre line expresses cre in renal cortical stroma, nephron progenitors and Tbx18-positive peri-Wolffian duct stroma).…”
Section: Introductionmentioning
confidence: 98%
“…Recent genetic studies in mice further support this notion and demonstrate that, in the absence of Fgfr1, there is a specific requirement for the c isoform of Fgfr2 in the development of the metanephric mesenchyme, including the maintenance of the Six2 and Pax2 progenitor compartments. Taken together, these data suggest that early nephron progenitors might rely, in part, on FGF receptor/ligand signaling that acts in an autocrine manner for their maintenance (Sims-Lucas et al, 2011).…”
Section: Research Articlementioning
confidence: 78%
“…A previous study (18) revealed that Pax3cre-mediated loss of Fgfr2 and concurrent loss of Fgfr1 in the kidney metanephric mesenchyme led to severe defects in metanephric patterning due to excessive apoptosis and aborted ureteric bud induction; moreover, the mice failed to express early (and critical) markers of the metanephric mesenchyme, including Six2, Sall1, and Pax2, and had severely attenuated glial cell line-derived neurotrophic factor levels, likely leading to ureteric induction defects (18). A followup study (23) revealed that while the IIIc isoform of Fgfr2 was most responsible for the early kidney defects seen in Pax3cre-Fgfr1 and Fgfr2 combined mutants, Fgfr2IIIb (the "epithelial" isoform) had an unexpected minor role in mesenchymal development.…”
Section: Discussionmentioning
confidence: 94%